Perbandingan Ketebalan Media Terhadap Luas Permukaan Filter Pada Biosand Filter Untuk Pengolahan Air Gambut - Eryan Chintya Debby; Lita Darmayanti; Yohanna Lilis Handayani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Clean water fullfilment become a common problem and yet to be solved  especially for isolated countryside area. Clean water can be defined as daily needs water and its quality should fullfil the requirement of healthy water based on laws and can be drinked when it is cooked.  High demand of clean water for peat area community  made this research to be important. The utilization of simple water treatment system is expected to solve the problem of clean water for the comunity. The purpose of this research is to determine effective thickness comparison of the surface filter. Treatment method used in this research is biosand filter with media of gravel and quartz sand. Water quality parameter tested are pH, color, solution degree, and organic contain (KmnO4). Statistical analysis used in this research is One Ways Varian Analysis (Anova). The result of the research shows that biosand filter able to improve the quality of peat. Thickness Comparison of the Surface Filter at the Biosand Filter have a significant influence on the value of the solution degree. Biosand filter can generate maximum efficiency in raising pH value of 33,90%, lowering peat water solution level of 82,56 %, lowering peat water colour value of 87 ,98 % and also lowering organic content of 83,88 %. Keywords : peat water, biosand filter, sand, gravel